Pemilu yang Adil: Strategi Penanganan Pidana Pemilu di Indonesia - Larasati Khoirunnisa; Siti Fatimah; Muhammad Adib Alfarisi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
General elections in Indonesia are carried out with a democratic mechanism to elect people’s representatives or leaders. Althought democracy is not the same as general elections, general elections are an important component of democracy that must also be held democratically. Article 22 E of the 1945 Republic of Indonesia Law serves as the main legal basis for general elections. This is intended to produce members of the DPR, DPD, DPRD, and members of the DPR at the district, provincial, and central levels. One of the main mandates of the constitution is to create democratic and quality elections. However, fraud, violations, and abuse of power continue to occur during the implementation of general elections. Money politics is currently a strong legal problem and continues to increase every year, making it one of the practices that damage democracy in Indonesia. General elections or abbreviated as elections are one way to conduct elections, in Islamic law the election is permissible or permissible, but in its implementation it must still be in accordance with sharia provisions and not cause harm. This stdy uses a normative legal research type that examines applicable laws and regulation. The conclusion of this study is that democracy has limited the opportunities for money politics practices, so it is necessary to enforce regulations to prevent and control money politics from occurring in the 2024 simultaneous elections, and the role and efforts of Bawaslu are needed to directly eradicate money politics in the 2024 elections by forming a money politics movement down to the village level.